Lactadherin orthologs inhibit migration of human, porcine and murine intestinal epithelial cells. Issue 4 (15th May 2017) - Nyegaard, Steffen; Andreasen, Trine; Rasmussen, Jan Trige
Abstract: Lactadherin was originally described due to its appearance in milk, but is abundantly expressed especially by professional and nonprofessional phagocytes. The proteins has been shown to have a multitude of bioactive effects, including inhibition of inflammatory phospholipases, induction of effero‐ and phagocytosis, prevent rotavirus induced gastroenteritis, and modulate intestinal homeostasis by regulating epithelial cell migration. The level of expression seems to be important in a row of serious pathologies linked to the intestinal epithelial barrier function, vascular‐ and autoimmune disease. This study examines the ability of lactadherin to modulate migration of intestinal epithelium. A cell exclusion assay is used to quantify the ability of human, bovine and murine lactadherin orthologs to affect migration of primary small intestine epithelium cells. Previous reports show that recombinant murine lactadherin stimulate rat small intestine cell migration. The present study could not confirm this. Conversely, 10 μg/ml lactadherin inhibits migration. Therefore, as lactadherins enteroprotective properties is well established using in vivo models we conclude that the protective effects are linked to lactadherins ability operate as an opsonin, or other modulating effects, and not a direct lactadherin‐cell induction of migration. Thus, the molecular mechanism behind the enteroprotective role of lactadherin remains to be established. Abstract : Lactadherin is a bioactive protein expressed in various tissues including phagocytes and known to exhibit beneficial effects in relation to gastrointestinal health. It has been proposed that lactadherin increases intestinal healing directly by enhancing the migration rate of intestinal cells, however here we show that neither human, bovine nor recombinant murine lactadherin increase the migration of intestinal cells. On the contrary, inhibition is observed at the maximal doses indicating that the beneficial effects likely relate to lactadherin's other bioactive properties.